2021
DOI: 10.1186/s12942-021-00282-0
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing of environmental risk factors for malaria in different geographic contexts

Abstract: Background Despite global intervention efforts, malaria remains a major public health concern in many parts of the world. Understanding geographic variation in malaria patterns and their environmental determinants can support targeting of malaria control and development of elimination strategies. Methods We used remotely sensed environmental data to analyze the influences of environmental risk factors on malaria cases caused by Plasmodium falciparu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 83 publications
(96 reference statements)
0
22
0
3
Order By: Relevance
“…When comparing our results to similar studies that utilize exposures in BRT models for predicting malaria occurrence, both at large (Sinka et al, 2010) and small (McMahon et al, 2021;Solano-Villarreal et al, 2019) spatial contexts, we observe partial correspondence. These studies used lower-resolution surface water maps and reported low importance of surface water predictors.…”
Section: Surface Water Versus Precipitation Predictorsmentioning
confidence: 51%
See 2 more Smart Citations
“…When comparing our results to similar studies that utilize exposures in BRT models for predicting malaria occurrence, both at large (Sinka et al, 2010) and small (McMahon et al, 2021;Solano-Villarreal et al, 2019) spatial contexts, we observe partial correspondence. These studies used lower-resolution surface water maps and reported low importance of surface water predictors.…”
Section: Surface Water Versus Precipitation Predictorsmentioning
confidence: 51%
“…Both "Classic" scenarios (5, 6) followed a pattern reported in similar studies, where surface water predictors contribute relatively little to model performance (McMahon et al, 2021;Sinka et al, 2010;Solano-Villarreal et al, 2019) et al, 2021), a short distance to river at the observation location may not be representative of the dispersal mechanisms at all possible locations of transmission. In contrast, Average Distance to Water represents the general location of water apropos land and the connectivity of waterbodies throughout the set spatial context, and by using multiple sizes of the spatial context and different persistencies of water this is done for more than one spatial context and waterbody temporality.…”
Section: Surface Water Versus Precipitation Predictorsmentioning
confidence: 66%
See 1 more Smart Citation
“…This study [ 34 ] focused on geographical factors affecting malaria and analyzed the other factors that can control malaria transmission. Remote sensing was used to gather data on environmental factors affecting malaria in Ethiopia’s two different geographical locations.…”
Section: Related Workmentioning
confidence: 99%
“…Although there are universal malaria interventions such as bed nets and access to prompt diagnosis and treatment for pregnant women in malaria-endemic settings, universal access to sanitation and hygiene should be implemented to prevent malaria and helminths co-infection in women of reproductive age and schoolchildren in endemic settings [157]. Moreover, improved diagnostic tools are required to better quantify the burden of malariahelminth co-infection, as this might help understand the burden of these infections for evidence-based planning and implementation of integrated control and elimination of both malaria and helminthic infections in co-endemic areas [158]. Future malaria vaccine development efforts might also need to understand the immune modulation in malariahelminth co-infection for better consideration of the effect of the helminth-malaria infection in vaccine immunogenicity [159].…”
Section: Optimisation Of Anti-malarial and Anti-helminthic Infections...mentioning
confidence: 99%